Perilaku Petani Kentang Terhadap Risiko Produksi di Desa Sumberejo Kecamatan Ngablak Kabupaten Magelang - Loho, Michelle Angellina; Yuliawati, Yuliawati (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Farmers always have hope and keep trying despite the risks involved in farming. Differences in farmer behavior and risk aversion will affect decision-making in the use of inputs in farming, which in turn will affect farmers' productivity and income levels. This study aims to analyze the behavior of potato farmers towards production risk in Sumberejo Village, Ngablak Subdistrict, and determine the factors that influence it. The sample size was 38 potato farmers from Sumberejo village who are members of Ngesti Subur, Sumber Makmur, and Bumi Lestari farmer groups. The sampling technique used was simple random sampling. The method of analysis used is the Moscardi and de Janvry model with the K(S) formula, and multiple linear regression to determine the factors that have a significant effect. The results of this analysis show that 76.32% of potato farmers in Sumberejo Village have risk-averse behavior (risk averter) and 23.68% have risk neutral behavior (risk neutral). One example that shows the risk-averse behavior of potato farmers in Sumberejo Village is the cooperation built with PT Indofood Sukses Makmur Tbk, so that the sales and income of these farmers are more secure. The factor that influences farmer behavior is land area. The resulting effect value is negative, meaning that the larger the land area owned, the lower the value of potato farmers' behavior towards production risk (K(S)).